Analysis and role of oligosaccharides in milk - L. Renee Ruhaak* & Carlito B. Lebrilla* (BMB Reports, 2012)
Milk is an important fluid in glycobiology because it contains anumber of short carbohydrate chains either free or asglycoconjugates. These compounds as a class are the mostabundant component and benefit the infant by developing andmaintaining the infant’s gut flora. New and emerging methodsfor oligosaccharide analysis have been developed to study milk.These methods allow for the rapid profiling of oligosaccharidemixtures with quantitation. With these tools, the role ofoligosaccharide in milk is being understood. They further pointto how oligosaccharide analysis can be performed, which untilnow has been very difficult and have lagged significantly thoseof other biopolymers.